2017
DOI: 10.21098/jimf.v3i1.709
|View full text |Cite
|
Sign up to set email alerts
|

Bank Run and Stability of Islamic Banking in Indonesia

Abstract: Bank run is an important economic phenomenon which increasingly occurred in in modern banking system and potentially threatened banking stability as it could trigger a banking crisis. However, most studies related to bank run focus on the occurrence of bank run in conventional banking system. Very few of them discuss the bank run phenomenon under Islamic banking system or dual banking system where Islamic banks jointly operating with conventional banks. Therefore, this study attempts to analyze the determinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…The research accepts the first hypothesis and confirms the positive impact of performance expectancy on the intention to use online platform to pay Zakah and Sadaqah. These findings are consistent with several previous studies including, (Khechine et Kasri and Sosianti, 2023). This finding suggests that using the online payment platforms for Zakah and Sadaqah can assist Zakah payers to improve their performance, through making faster payments from anywhere with lower costs compared to payment through traditional channels.…”
Section: Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The research accepts the first hypothesis and confirms the positive impact of performance expectancy on the intention to use online platform to pay Zakah and Sadaqah. These findings are consistent with several previous studies including, (Khechine et Kasri and Sosianti, 2023). This finding suggests that using the online payment platforms for Zakah and Sadaqah can assist Zakah payers to improve their performance, through making faster payments from anywhere with lower costs compared to payment through traditional channels.…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…Based on this finding, it can be suggested that Zakah and Sadaqah online donors are often motivated by encouragement from friends, family, and other influential people around them. This result is consistant with previous studies, including (Farouk et al, 2017;Bin-Nashwan et al, 2023;Kasri and Sosianti, 2023). They all concluded that social influence helps in anticipating donors' intentions to use a system or technology that their peers suggest.…”
Section: Discussion Of Resultssupporting
confidence: 88%
“…In examining the effectiveness or impacts of regulations on banking performance, particularly from the banks’ financing side, there are at least two broad studies that can be highlighted. The first is related to the role or direct impact of banking regulations on the performance of banks (Barth et al , 2001), while the second is related to the indirect role or impact of variables such as the fundamental factors of other banks and macroeconomic variables (Kasri et al , 2017) on the banks’ performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding agrees with those of Mohamad et al (2013) and Boukhatem and Ben Moussa (2018), which showed that the behavior of Islamic banking in terms of liquidity is procyclical and positively affects the economy. Likewise, Ibrahim (2016), Kasri et al (2017) and Zulkhibri and Sakti (2018) showed that the presence of Islamic banking can stabilize an economy during periods of liquidity shock. This result provides support for a macroprudential approach in addition to the microprudential approach as part of banking regulations.…”
Section: Estimation Resultsmentioning
confidence: 99%